2021
DOI: 10.1007/s40429-021-00359-7
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory and Immunologic Effects of Electronic Cigarettes

Abstract: Purpose of Review Although e-cigarettes have become popular, especially among youth, the health effects associated with e-cigarette use remain unclear. This review discusses current evidence relating to the cardiovascular, pulmonary, and immunological effects of e-cigarettes. Recent Findings The use of e-cigarettes by healthy adults has been shown to increase blood pressure, heart rate, and arterial stiffness, as well as resistance to air flow in lungs. Inhalation of e-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 100 publications
0
24
0
13
Order By: Relevance
“…Emerging data indicate that e-cig use may adversely affect the pulmonary and cardiovascular systems [24,[35][36][37][38][39]. Also, limited evidence exists on the potential of e-cigs to cause carcinogenic effects [32,33,[40][41][42][43][44][45].…”
Section: Health Consequences: Smoking Vs Vapingmentioning
confidence: 99%
“…Emerging data indicate that e-cig use may adversely affect the pulmonary and cardiovascular systems [24,[35][36][37][38][39]. Also, limited evidence exists on the potential of e-cigs to cause carcinogenic effects [32,33,[40][41][42][43][44][45].…”
Section: Health Consequences: Smoking Vs Vapingmentioning
confidence: 99%
“…A recent review highlighted that the use of e-cigs determines negative changes in cardiovascular, respiratory, and immune systems, increasing blood pressure, heart rate, arterial stiffness, and resistance to air flow in lungs and causing the production of immunomodulatory cytokines. Results from animal and in vitro studies confirmed that long-term exposure to e-cigs is associated to significant health risks for these systems [ 11 ]. Moreover, since 2019, a new epidemic of a syndrome called e-cigarette or vaping product use-associated lung injury (EVALI) has affected thousands of U.S. individuals [ 12 ].…”
Section: Introductionmentioning
confidence: 95%
“…The characteristic health risks of ENDS toxicity cannot be readily extrapolated based on the relatively fewer numbers or levels of toxins compared with cigarette smoke 4–6. In addition, ENDS contain compounds not otherwise present in combustible cigarettes, such as the solvents propylene glycol (PG) and glycerol, and flavourants that may pose unique health risks through continuous use.…”
Section: Introductionmentioning
confidence: 99%